Rubrics and Academic Performance in English as a Foreign Language Teaching: Assessing Writing Tasks - Monica Narvaez; Edison Salas; Elsa Basantes; Nancy Rodriguez; Maria Escobar (European Scientific Journal, ESJ, 2019)
Using rubrics in foreign language teaching has become a popular procedure among academics around the world. Rubrics are useful tools to improve educational in-class processes, as well as, to assess students’ learning outcomes. This study aims to determine whether the application of rubrics as an assessment tool influences eighth-grade foreign language students’ Academic Performance.A diagnostic survey was applied to the teachers of the foreign language department at the high school to determine which assessment tools were used to assess and grade students’ writing class work. Twenty-eight students of eighth grade, classroom “D” (octavo año de educación básica class "D") and foreign language teachers of Unidad Educativa Colegio Militar Nº6 “Combatientes de Tapi (UECMCT), Riobamba, Ecuador, participated in the study. The Academic Performance data of the students was collected during the second term of the second five-month school period (quimester) and analyzed through figures and tables, where a written activity was assessed without the application of a rubric. The results of this first students’ performance assessment showed that many students were not proficient in learning. Subsequently, an assessment rubric was elaborated and applied as an evaluation instrument of a written activity during the third term of the second quimester. In this opportunity, as a result, a large number of students improved their performance and achieved the expected learning outcomes. The application of this assessment tool not only enhanced the Academic Performance of the students but also allowed the teacher to facilitate the assessment process.